Development of High-Altitude Balloon Platform for Education, Experiment and Research in Science, Technology and Engineering - Pemmavit Sutthikarn; Sorawat Chivapreecha; Thitaphan Jongsataporn; Akraphon Trirat (My University, 2023)
This paper presents a study and development of high-altitude balloon platform for education, experiment and research in science, technology and engineering where it is necessary to conduct the experiments in the atmosphere above stratosphere.Moreover, the high distance can also be used to simulate near space conditions, used in experiments or measurements of various physical quantities in high-level atmospheric physics including use in the measurement for meteorology.The platform consists of 2 major parts: 1) Calculations involving balloon for mission planning such as ability to carry payloads for testing, lifting force, total time the balloon can stay afloat for the mission, ascent rate, etc.It also includes designing a parachute for bringing all payloads back to Earth after complete a mission.2) Balloon coordinate tracking system and communication system which serves to transmit coordinates for tracking and other necessary measurement data to the ground.This is to keep track of the balloon's travel position during the mission, including the vertical displacement and the horizontal displacement caused by wind current/direction, and also used to track the last stop for recovery mission.The main contribution and relevant knowledge for the mission that use high-altitude balloon platform for testing will be explained in this paper.Along with conducting some experiments on the use of a high-altitude balloon platform to test engineering prototype of the 1U CubeSat (KMITL-CubeSat), we can visualize its application to the KMITL-CubeSat and also apply to other tests in the work and mission of science, technology and engineering in other areas further.
Keywords: Aerospace Engineering and Energy Systems